Validation of a Clinical Scoring System for Outcome Prediction in Dogs with Acute Kidney Injury Managed by Hemodialysis - G. Segev; C. Langston; K. Takada; P.H. Kass; L.D. Cowgill (Journal of Veterinary Internal Medicine, 2016)
Background A scoring system for outcome prediction in dogs with acute kidney injury (AKI) recently has been developed but has not been validated. Hypothesis The scoring system previously developed for outcome prediction will accurately predict outcome in a validation cohort of dogs with AKI managed with hemodialysis. Animals One hundred fifteen client‐owned dogs with AKI. Methods Medical records of dogs with AKI treated by hemodialysis between 2011 and 2015 were reviewed. Dogs were included only if all variables required to calculate the final predictive score were available, and the 30‐day outcome was known. A predictive score for 3 models was calculated for each dog. Logistic regression was used to evaluate the association of the final predictive score with each model's outcome. Receiver operating curve (ROC) analyses were performed to determine sensitivity and specificity for each model based on previously established cut‐off values. Results Higher scores for each model were associated with decreased survival probability (P < .001). Based on previously established cut‐off values, 3 models (models A, B, C) were associated with sensitivities/specificities of 73/75%, 71/80%, and 75/86%, respectively, and correctly classified 74–80% of the dogs. Conclusions and Clinical Relevance All models were simple to apply and allowed outcome prediction that closely corresponded with actual outcome in an independent cohort. As expected, accuracies were slightly lower compared with those from the previously reported cohort used initially to develop the models.